Administrative legal principles in the system of anti-corruption measures - Opanasenko, N. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
Analyzed in forensic scientific approaches to identify traces of the crime. Presented the typical traces of organized crime of swindlers in the housing. Outlined documentary sources of fraud. Defined material, ideal and virtual tracks of fraud in housing construction.